Learning during the covid-19 pandemic: Analysis of e-learning on sports education students - Gumantan, Aditya; Nugroho, Reza Adhi; Yuliandra, Rizki (Journal Sport Area, 2021)
This study aims to determine the level of achievement in each competency given to students and to find out the average percentage of post-e-learning student scores. The research method used is quantitative with descriptive statistical techniques. The study population is sports education students in class 2017, 2018 and 2019, active students, with a sample of 10% of the population, the determination of this sample is based on purposive sampling. Data collection techniques use test instruments, in the form of questions and semester exam results. The research data analysis technique uses descriptive statistical techniques obtained during the 2019-2020 semester, namely the value of the Final Semester Examination, after feeling that it is sufficient to obtain data and process it will get the results of the research. The results of the study find that effective learning is seen from 83% of students getting course scores with an average of above 75 at the time of the final even semester examinations in 2019-2020, and it can be concluded that the effectiveness of e-learning in Sports Education students at the Indonesian Teknokrat University is successful. with a student passing rate above 80%. It is hoped that this e-learning process will be further developed with a better platform for the sake of facing future generations where the role of technology is a major thing in facing the changing times.